Investigation of Possible Positive Effects of Arbutin Application in Experimental Colitis Model - Bıyıklı Alemdar, Merve; Şirinyıldız, Ferhat; Coşkun, Adil; Meteoğlu, İbrahim and Taşkıran, İsmail and Kandemir, Altay and Hadi Yaşa, Mehmet (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study aimed to investigate the possible positive effects of arbutin in a trinitrobenzene sulfonic acid (TNBS)- induced experimental colitis model, to compare it with mesalazine, which is used in treating inflammatory bowel disease and to observe the effect of its concomitant use. Materials and Methods: Forty Wistar albino species male rats were randomized into 5 groups as control, colitis, colitis+arbutin (Arb), colitis+mesalazine (Mes), and colitis+mesalazine+arbutin (M+A). Proinflammatory cytokines [interleukin (IL)-6, IL-1β, tumor necrosis factor alpha (TNF-α)] and oxidant/antioxidant parameters [malondialdehyde (MDA), superoxide dismutase inhibition (SOD) inhibition, myeloperoxidase (MPO), and catalase, glutathione peroxidase (GPx)] were processed from the samples. Histopathological evaluation evaluated goblet cell reduction, cellular infiltration, and mucosal loss. Results: When the treatment groups and the TNBS group were compared, statistical significance was achieved in MDA, MPO, SOD inhibition, GPx values, IL-6, IL-1β and TNF-α levels. Histopathological evaluation revealed a statistically significant decrease in the mucosal loss value in the group where mesalazine and arbutin were used together compared to the TNBS group. Conclusion: Our study’s results elaborated that using arbutin alone or in combination with mesalazine produced positive effects in colitis-induced rats. Cite this article as: Alemdar MB, Şirinyıldız F, Coşkun A, et al. Investigation of possible positive effects of arbutin application in experimental colitis model. Turk J Gastroenterol. 2024;35(7):523-531.